Policy Analysis of the Jakarta Smart Card Program in Elementary Schools - Fathur Rahman Baeny; Trisni Handayani (Universitas Negeri Semarang, 2025)
This study aims to analyze the Jakarta Smart Card (KJP) Program policy at SDN KP 11 JT, which includes the planning, implementation, and evaluation of the program. The KJP Program is an effort by the Jakarta Provincial Government to ensure access to education for students from underprivileged families through educational cost assistance, this action also driven by the fundamental right of every person to receive education. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and documentation. The informants consisted of the school principal, teachers, school operator, and parents of KJP recipients. The results of the study show that the role of the school in planning is limited to data validation from DTKS and outreach to parents. In the implementation stage, the school provides guidance on fund usage and conducts informal monitoring through homeroom teachers. Evaluation is carried out periodically, although the school's authority over program implementation is limited. The KJP Program is considered to have a positive impact on students' educational continuity and ease the economic burden on families. This study recommends the need to strengthen parental education and a more formal monitoring system so that the aid is well-targeted and effective.